2017
DOI: 10.18632/oncotarget.17410
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer in patients with heart failure who use digoxin: a 10-year follow-up study and cell-based verification

Abstract: Heart failure (HF) is the leading cause of death in the world and digoxin remains one of the oldest therapies for HF. However, its safety and efficacy have been controversial since its initial use and there is uncertainty about its long-term efficacy and safety. Recently, the repositioning of cardiac glycosides is to function in anti-tumor activity via multiple working pathways. It is interesting to compare the potential effects of digoxin in clinical patients and cell lines. First, we analyze patient informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although the anti-CA effect of digoxin is suspected in basic science, in a retrospective cohort study with a 10-year follow-up, taking digoxin increased the risk of CA, including breast, liver, and lung CA. 38 Although the risk of CA from antihypertensive drugs (e.g., ACE inhibitors, angiotensin-receptor blockers, calcium-channel blockers, β-blockers and diuretics) has been much debated, 15,35-37 recent network meta-analyses using 70 randomized controlled trials with 324,168 patients, suggested no evidence of CA increase or CA-related death, except for a combination of ACE inhibitor and angiotensin-receptor blocker, which may increase CA risk. 39…”
Section: Underlying Mechanism Of the Relationship Between Ca And Hfmentioning
confidence: 99%
“…Although the anti-CA effect of digoxin is suspected in basic science, in a retrospective cohort study with a 10-year follow-up, taking digoxin increased the risk of CA, including breast, liver, and lung CA. 38 Although the risk of CA from antihypertensive drugs (e.g., ACE inhibitors, angiotensin-receptor blockers, calcium-channel blockers, β-blockers and diuretics) has been much debated, 15,35-37 recent network meta-analyses using 70 randomized controlled trials with 324,168 patients, suggested no evidence of CA increase or CA-related death, except for a combination of ACE inhibitor and angiotensin-receptor blocker, which may increase CA risk. 39…”
Section: Underlying Mechanism Of the Relationship Between Ca And Hfmentioning
confidence: 99%
“…As oncogenesis requires long duration, it may be better to prolong an interval more. Reportedly, during the 10-year follow-up period, an increased risk of cancer was observed in patients receiving digoxin 40 . Another report demonstrated that the risk of cancers associated with both long- and short-term digoxin uses was controversial 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, amiodarone may be associated with an increased risk of incident cancer, especially in men (Su et al, 2013). Therefore, possible concomitant medications might interfere with the interpretation of the previous studies (Chung et al, 2017;Xie et al, 2017). The current study used propensity-score matching to minimize the effect of concomitant medications.…”
Section: Cancer Risk Of Digoxin Use Was Influenced By Concomitant Medmentioning
confidence: 99%
“…Firstly, some studies had confounding by indication, a phrase that refers to a situation where patient characteristics, rather than the intervention, are independent predictors of outcome ( Cnossen et al, 2018 ). As a consequence, patients exposed and not exposed to digoxin might not be comparable, which hindered the relational inference ( Biggar et al, 2012 ; Chung et al, 2017 ). Moreover, the previous studies neglected the possible cancer-preventive effect of concomitant medications, such as aspirin, ACEI, and ARB ( Chung et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation